Access to Information on Toddler Family Development Program and Family Participation in Child Growth and Development - Dhammayanti, Dita; Simbolon, Demsa; Ervina, Lissa; Fauzi, Yusran (UI Scholars Hub, 2025)
The comprehension of the Toddler Family Development (TFD) Program among families in Indonesia remains limited, likely due to insufficient access to information and low participation rates. Limited participation can negatively affect a family’s ability to support optimal child growth and development. This study examined the relationship between access to information on the TFD Program and family participation in child growth and development. Using secondary data from the 2019 Program Performance and Accountability Survey in Indonesia, the cross-sectional analysis included 21,497 respondents. The results revealed an association between access to information on the TFD Program and family participation in child growth and development (OR: 1.53; 95% CI: 1.34–1.75). Families with limited access to TFD program information were 1.5 times more likely not to engage in child growth and development and parenting activities. Engaging in the TFD Program can help parents with the better growth and development of their children under the age of five.